Symbolic Representation and Semiotic Analysis of Roland Barthes on Buya Yahya's Ramadan Recitation - Algholayani, Muchammad Mustofa; Zukriyah, Luluk Fikri (Academia Publication, 2025)
This article analyzes the symbolic representation of Buya Yahya’s da’wah messages in his Ramadan sermons broadcasted on the Al-Bahjah YouTube channel, employing Roland Barthes’ semiotic framework. The study aims to uncover the layers of meaning embedded in Buya Yahya’s messages, which are conveyed not only through verbal content but also through symbolic language and structured emotional expression. Utilizing a qualitative descriptive method, data were collected through content observation and verbatim transcription. The analysis reveals that each da’wah quote comprises three layers of meaning: denotative (literal), connotative (emotional and cultural), and mythological (ideological), all of which construct an inclusive, spiritual, and transformative Islamic discourse. The myths formed through Buya Yahya’s messages emphasize selective companionship, spiritual preparedness, digital ethics, and optimism for personal transformation. His da’wah practice goes beyond religious instruction, functioning as a mechanism for shaping collective consciousness through symbolic systems in the digital media era. These findings contribute to the development of Islamic communication studies, digital da’wah strategies, and communication education grounded in symbolism and narrative.